PENGARUH STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PT NICKERSON STAR MULTI PERKASA MEDAN - Sunarji Harahap; Valerie Tanjaya; Elidawati (STIE-PMCI, 2021)
PT. Nickerson Star Multi Perkasa Medan is engaged in fertilizer and its operational activities include buying and selling of fertilizers. The purpose of this study was to determine and analyze the effect of asset structure and sales growth on capital structure with profitability as an intervening variable at PT Nickerson Star Multi Perkasa Medan. The population to be the sample of this study is 48 data on fixed assets, total assets, sales, total debt, equity, net profit of PT Nickerson Star Multi Perkasa Medan for the period 2016-2019. This research data collection technique using document analysis of the financial statements of PT Nickerson Star Multi Perkasa Medan for the period 2016-2019. and literature review which is the reference for this study. Path analysis is used to determine the relationship pattern of the variables but cannot be used to confirm or reject the hypothesis. The results showed that the asset structure has a positive and significant effect on the capital structure at PT Nickerson Star Multi Perkasa Medan. Sales growth has a negative and significant effect on the capital structure of PT Nickerson Star Multi Perkasa Medan. Asset structure has a significant negative effect on profitability at PT Nickerson Star Multi Perkasa Medan. Sales growth has a significant negative effect on profitability at PT Nickerson Star Multi Perkasa Medan. Profitability has no effect on the capital structure of PT Nickerson Star Multi Perkasa Medan. Keywords: Asset Structure, Sales Growth, Profitability and Capital Structure.